Punishing and Forgiving: Contributions of Deconstruction to Contemporary Debates on Justice - Quintana Dominguez, Idoia (ETHICS IN PROGRESS, 2026)
This article challenges the widespread tendency to frame forgiveness either as a moral alternative to punishment or as a practice set in opposition to and disconnected from criminal law. It instead focuses on the tension between punishment, forgiveness and justice by examining the work of Jacques Derrida. The paper argues that the prevailing readings of Derridean forgiveness as unconditional and alien to any legal logic overlook its place within the broader deconstructive task, particularly in the constitutive tension between law and justice. In light of this reconsideration, the article explores the critical scope of deconstruction to interrogate the role of forgiveness, both within punitive logics and within frameworks that advocate responses to harm beyond punishment, including transitional justice and restorative justice.